Social congratulations and politics in Andalusia (138-897 AH / 755-1492 AD) Social and political congratulations in Andalusia - Afaaq Lazeem Abdlu Laeef (Zien Journals, 2022)
The research studies the phenomenon of congratulations, a logical and analytical study. The research is divided into two sections. The first topic is "Congratulations in Islam" and the definition of "Congratulations" in language, terminology, etiquette, rules of congratulations, general words used in congratulations, and words synonymous with "Congratulations." With victories and social congratulations, including congratulations on the two holidays, congratulations on the newborn and circumcision, congratulations on marriage, congratulations on coming from travel, congratulations on recovery from diseases, congratulations on the new year, congratulations among the dhimmis in Andalusia, the effect of congratulations on the souls of the public, and the summary of the research
Keywords: Legitimate occasion; Congratulations